In Plant Assessment of Lactic Acid Intervention in Variety Meats Through the Beef Processing Line - Moya A., Eduardo J. (Zamorano: Escuela Agrícola Panamericana, 2020, 2020)
Beef industries continuously seeks interventions that may reduce bacterial loads in their products to increase shelf life and ensure beef product wholesomeness. This in-plant validation study was conducted to evaluate the effect of spray lactic acid interventions in beef variety meats. Lactic acid solution (2 to 5%) was applied to variety meats by spray application ≥ 103.42 kPa for 5 s. Samples were collected in plant during the processing line by swabbing 500 cm2 surface area of meat before and after lactic acid applications. A total of 108 samples were collected (54 before and 54 after) for beef liver, cheek, and heart. All samples were shipped to Texas Tech University´s food Microbiology laboratory for microbiological analysis. Composites of three samples were made by adding 3 mL of each sample to a sterile test tube until reaching 9 mL. All composites were serially diluted and plated to determine total aerobic plate counts (APC), coliform counts and generic E. coli counts using 3M APC Petrifilm, 3M Coliform/E. coli Petrifilm, respectively. Duplicates were made of each Petrifilm and were incubated at 37 °C. All samples were converted to CFU per cm2 before statistical analysis. Treatment with lactic acid (2-5%) spray was lower (P < 0.005) in APC, generic E. coli and total coliforms microbial loads after the intervention on beef cheek, heart, and liver. Therefore, lactic acid (2-5%) spray intervention reduces Aerobic Plate Count, Total Coliforms and generic E. coli in beef cheeks, heart, and liver in the processing line.